Mindfulness-Based Nursing Intervention for Anxiety and Quality of Life in Palliative Cancer Care: A Quasi-Experimental Study - Ahmad Syaripudin (Media Publikasi Cendekia Indonesia, 2026)
Advanced cancer patients in palliative care frequently face severe existential anxiety and diminished quality of life (QoL). While managing this psychological distress is critical, pharmacological interventions often present adverse side effects. This quasi-experimental study aimed to evaluate the effectiveness of a structured Mindfulness-Based Nursing Intervention (MBNI) on anxiety levels and QoL among patients receiving palliative cancer care. The study evaluated anxiety using the Hospital Anxiety and Depression Scale (HADS-A) and QoL via the EORTC QLQ-C30 Global Health Status scale. The participant cohort predominantly consisted of females (60.0%) and individuals diagnosed with stage IV malignancies (63.3%), with lung cancer being the most frequent primary site (30.0%). Data were analyzed utilizing the non-parametric Wilcoxon signed-rank test. To prevent inflation and account for paired data, clinical effect sizes were calculated using the standardized mean difference adjusted for paired variances (dav). Following MBNI implementation, participants demonstrated statistically significant improvements across both primary endpoints (p < 0.001). The mean anxiety score notably decreased from a baseline of 20.0 ± 5.0 to 14.0 (Z = -4.512). Concurrently, the mean QoL score increased substantially from 50.0 ± 12.5 to 65.0 (Z = -4.287). The intervention produced a large, identical adjusted effect size of dav = 1.20 for both anxiety reduction and QoL enhancement. The MBNI represents a highly promising, non-pharmacological modality for mitigating severe psychological distress and optimizing global well-being. Integrating this structured protocol into holistic palliative nursing pathways is strongly recommended to ground fragile oncology patients amidst prognostic uncertainty.